ELSA Speak: Piquing Demotivated Students to Self-Improve Their Pronunciation with an AI-powered English Speaking Coach - Khalizah, Nur; Damanik, Emeliya Sukma Dara (Universitas Lancang Kuning, 2024)
The heightened global expectation of English proficiency is equally matched with the demand for students of this generation to be adept at handling technology, leading to the boom of artificial intelligence application in education. This paper is a contribution from a local teacher’s attempt to adapt and use an AI English speaking coach called ELSA Speak. This study determines the impact of using the app in enhancing junior high school students’ speaking skills through a pre-experimental study and establish a state-of-the-art understanding of the extent of the collective exploration of this AI. The first research design is a pre-experimental study and utilised the quantitative analysis approach, involving 23 third-grade pupils from MTs Zia Salsabila Percut Sei Tuan as the sample. The second research design is a systematic literature review of a total of 491 papers published from 2015 to 2024. Findings from the primary data proved that ELSA Speak app effectively enhances students' speaking proficiency in five aspects (grammar, vocabulary, pronunciation, fluency, and content) and successfully held the attention of students whose history prior to the use had very low motivation to learn and practice English as a foreign language. However, the systematic review revealed that this type of study is the furthest point of current investigation on ELSA Speak app, and thus calls for the need for more robust studies to develop a better understanding of whether the short-term success of using the AI can last for long-term and in what other ways can it be integrated into the teaching syllabus.